Analytical Methods for the Determination of Rosuvastatin in Pharmaceutical Formulations and Biological Fluids: A Critical Review - Ângelo, Marilene Lopes; Moreira, Fernanda de Lima; Morais Ruela, André Luís; Santos, Ana Laura Araújo; Salgado, Hérida Regina Nunes [UNESP]; de Araújo, Magali Benjamim (Taylor & Francis, 2018)
Rosuvastatin calcium (ROS), (Figure 1) belongs to the “statins” group, which is the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor. This drug is indicated for dyslipidemias treatment and can help to decrease the level of “bad cholesterol” and can consequently reduce the development of atherosclerosis and the risk of heart diseases. ROS was developed by Astra-Zeneca and it was approved in 2003 by the FDA in the United States. In 2015, under the trade name Crestor®, it was the fourth largest selling drug in the United States with sales above $5 billion. This study presents a literature review of analytical methods for the quantification of ROS in pharmaceutical preparations and biological fluids. The major analytical methods described in this study for ROS were spectrophotometry, high-performance liquid chromatography (HPLC) coupled to ultraviolet (UV) detection, and tandem mass spectrometry (LC–MS/MS).
Keywords: Analytical methods; HPLC; LC–MS/MS; rosuvastatin; spectrophotometry